2018
DOI: 10.1097/tp.0000000000002026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biomarkers Within the Initial 2 Years Posttransplant and 5-Year Kidney Transplant Outcomes

Abstract: Background An early posttransplant biomarker/surrogate marker for kidney allograft loss has the potential to guide targeted interventions. Previously published findings, including results from the Clinical Trials in Organ Transplantation (CTOT)-01 study, showed that elevated urinary chemokine CXCL9 levels and elevated frequencies of donor-reactive interferon gamma-(IFNγ)-producing T cells by enzyme linked immunosorbent spot (ELISPOT) assay associated with acute cellular rejection within the first year and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 40 publications
0
42
1
Order By: Relevance
“…However, a subsequent study with a longer follow-up (CTOT-17) showed that changes in eGFR between 3 or 6 months and 24 months better predicted 5-year graft loss than CXCL-9 measurement [ 64 ].…”
Section: Armentioning
confidence: 99%
“…However, a subsequent study with a longer follow-up (CTOT-17) showed that changes in eGFR between 3 or 6 months and 24 months better predicted 5-year graft loss than CXCL-9 measurement [ 64 ].…”
Section: Armentioning
confidence: 99%
“…The authors also concluded that 30% decline in eGFR between years 1 and 3 after kidney transplant is common and strongly associated with risks of subsequent death and death-censored graft failure, which mirrors findings in CKD (Clayton et al 2016 ). Faddoul et al reported results from clinical trials in organ transplantation (CTOT) 17 also identifying a 40% decrease in post-kidney transplant eGFR from 6 months post 2 years post-transplant as a surrogate for 5-year outcomes (Faddoul et al 2018 ).…”
Section: Egfr Declinementioning
confidence: 99%
“…Recent works have shown a strong association between positive pre-transplant d-sp ELISPOT and increased risk of BPAR after transplantation, particularly TCMR, and especially, in patients not receiving T-cell depleting induction therapies [ 8 , 14 , 18 ]. Faddoul G and colleagues [ 33 ] reported a close association between d-sp alloreactivity evaluated with d-sp ELISPOT and an increased risk of BPAR and worse graft function at 2 years in positive patients. Our current findings confirm and expand previous evidence in a larger cohort of patients, where the relationship between pre-transplant d-sp ELISPOT and a higher risk of BPAR was mainly driven by patients not induced with Thymoglobulin.…”
Section: Discussionmentioning
confidence: 99%